Impaired Potentiation of Theta Oscillations During a Visual Cortical Plasticity Paradigm in Individuals With Schizophrenia - Hamilton, Holly K.; Roach, Brian J.; Cavus, Idil; Teyler, Timothy J.; Clapp, Wesley C.; Ford, Judith M.; Tarakci, Erendiz; Krystal, John H.; Mathalon, Daniel H. (Frontiers in Psychiatry, 2020)
Long-term potentiation (LTP) is a form of experience-dependent synaptic plasticity mediated by glutamatergic transmission at N-methyl-D-aspartate receptors (NMDARs). Impaired neuroplasticity has been implicated in the pathophysiology of schizophrenia, possibly due to underlying NMDAR hypofunction. Analogous to the high frequency electrical stimulation used to induce LTP in vitro and in vivo in animal models, repeated high frequency presentation of a visual stimulus in humans in vivo has been shown to induce enduring LTP-like neuroplastic changes in electroencephalography (EEG)-based visual evoked potentials (VEPs) elicited by the stimulus. Using this LTP-like visual plasticity paradigm, we previously showed that visual high-frequency stimulation (VHFS) induced sustained changes in VEP amplitudes in healthy controls, but not in patients with schizophrenia (Cavus et al., 2012). Here, we extend this prior work by re-analyzing the EEG data underlying the VEPs, focusing on neuroplastic changes in stimulus-evoked EEG oscillatory activity following VHFS. EEG data were recorded from 19 patients with schizophrenia and 21 healthy controls during the visual plasticity paradigm. Event-related EEG oscillations (total power, intertrial phase coherence; ITC) elicited by a standard black and white checkerboard stimulus (∼.83 Hz, several 2-minute blocks) were assessed before and after exposure to VHFS with the same stimulus (∼8.9 Hz, 2 minutes). A cluster-based permutation testing approach was applied to time-frequency data to examine LTP-like plasticity effects following VHFS. VHFS enhanced theta band total power and intertrial phase coherence in healthy controls but not in the patients with schizophrenia. The magnitude and phase synchrony of theta oscillations in response to a visual stimulus were enhanced for at least 22 minutes following VHFS, a frequency domain manifestation of LTP-like visual cortical plasticity. These theta oscillation changes are deficient in patients with schizophrenia, consistent with hypothesized NMDA receptor dysfunction.